PERFORMANCE AND SUSTAINABILITY MODEL OF WAJIT CILILIN MICRO, SMALL AND MEDIUM ENTERPRISES IN CILILIN SUB-DISTRICT WEST BANDUNG REGENCY - Susana Supiani Herawati (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
The decrease of performance and sustainability of wajit cililin business in Cililin Sub-District is the basis for this research. This study determines the effect of literacy, inclusion, and financial management on the performance and sustainability of wajit cililin business along with the supporting and inhibiting factors for business success. The type of research is explanatory sequential Mix Method using SEM-PLS analysis tool. Samples were collected using probability sampling with a simple random sampling technique of 35 wajit cililin small business units to be tested. In addition, the sample was taken based on certain criteria using purposive sampling method to answer the research issues raised. The research result confirmed that literacy, inclusion and financial management significantly positively affect business performance and sustainability. Meanwhile, small businesses' performance and sustainability model is designed using The House Model Theory consisting of a roof, pillars and foundation. The design of this model can be implemented optimally by small business actors for wajit cililin products to minimize the occurrence of risks and obstacles faced. For the government as a regulatory function to formulate policies, service institutions as an intermediary function that has a role in economic growth and the cililin community as a driver in the implementation and development of literacy, inclusion and management of the small financial business.